(3GdJQHjI Ydi Mbhb GdWad (B: (3eYQaI GdJdGejP hGdCSGJPI hGdCgd hehGbage, hGbY Mbhb GdWad aj GdeOQSI hGdeLJeYs - (3eNGjd, Gjdjs ((3HjQhJs (3OGQ SGFQ GdeTQbs, 2015)
(3MbGFb egeI JXgQgG gPg GdOQGSI Yf hGbY Mbhb GdWad aj GdeOGQS GdQSejI hGdNGUI aj eOjfI HjQhJ, dG SjeG Ydi eSJhi eYQaI GdJdGePI hGdGSGJPI hGdGgd HMbhb GdWad(B. (3hdYd CHQR gPg GdMbGFb Cf LejY GdGWQGa GdeYfjI HTDhf JQHjI GdWad aj dHfGf JfbUge gPg GdeYQaI(B...s
Keywords: (3Mbhb GdWad (B-- (3dHfGf (B-- (3OQGSIs; (3GdJQHjI hGdJYdje (B-- (3dHfGf (B-- (3Mbhb GdWad (B--(3OQGSIs; (3OQGSI (B-- (3Mbhb GdWad (B-- (3GdeOGQSs